2023
DOI: 10.3390/lubricants11090388
|View full text |Cite
|
Sign up to set email alerts
|

A Finite Element Analysis of Cold Deep Drawing of Al Alloy Considering Friction Condition and Corner Design of Plunger

Warda Bahanan,
Siti Fatimah,
Jae Hoon Go
et al.

Abstract: This study presents an innovative methodology that integrates experimental investigations with finite element simulations to ascertain the validity and reliability of Al 3104 sheet metals during cold deep drawing. Focusing on the nose plunger radius and coefficient of friction at a fixed speed and temperature (25 °C), five different scenarios are utilized to simulate the optimum parameters. Through a detailed strain history analysis from simulations, the initiation of bending in the corner is precisely identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Also studying friction conditions, Neto et al [10] used numerical simulations to study the influence of friction as a function of pressure on wrinkling in the deep drawing process. In the numerical and experimental study conducted on cold deep drawing, Bahanan et al [11] indicated that the friction coefficient has a significant influence on the process. They showed that rupture, in the form of tears or splits, can be avoided if the elements located near the die surface flow more easily compared to those near the punch.…”
Section: Introductionmentioning
confidence: 99%
“…Also studying friction conditions, Neto et al [10] used numerical simulations to study the influence of friction as a function of pressure on wrinkling in the deep drawing process. In the numerical and experimental study conducted on cold deep drawing, Bahanan et al [11] indicated that the friction coefficient has a significant influence on the process. They showed that rupture, in the form of tears or splits, can be avoided if the elements located near the die surface flow more easily compared to those near the punch.…”
Section: Introductionmentioning
confidence: 99%